Reef design influences habitat provision on a restored oyster reef - Beseres Pollack, Jennifer; Sugla, Monisha; Breaux, Natasha J.; Trackenberg, Stacy N.; Palmer, Terence A. (Frontiers in Marine Science, 2024)
Habitat restoration efforts are often limited by cost, making it important that available funds are used efficiently and effectively to achieve desired restoration goals. In this study, we evaluate habitat provision for oysters and motile epifauna on restored oyster reefs in a northwestern Gulf of Mexico estuary constructed with discrete high vertical relief (~0.6 m “reef mounds”) or continuous low vertical relief (<0.08 m “reef flats”). Habitat provision on reef mounds exceeded that on reef flats within one month of construction and supported 0.75x higher oyster density, 2x higher motile epifauna biomass, and 3.6x higher motile epifauna density one year after construction. Oyster density on reef mounds remained relatively high throughout the study period, with ~2x higher oyster densities than reef flats 18 months after construction and ~1.5x higher oyster densities by the end of the study. Both reef mounds and reef flats increased oyster and epifaunal densities compared to unrestored areas. Although on-reef oyster densities were higher on reef mounds than reef flats, the total restored oyster areal density and volumetric density was higher in restored reef flat areas, primarily because the restored flats area had no gaps within its restoration boundaries. Our findings have practical value for better predicting restoration outcomes and achieving desired restoration goals based on restored oyster reef height, with reef mounds maximizing on-reef oyster and epifaunal densities and reef flats maximizing the total number of oysters per area restored or volume of substrate purchased. Understanding the benefits and tradeoffs between restoration designs will allow resource managers to improve cost-efficiencies in future restoration projects.